Chop Joo Huat Grocery Ordering System - Yew, Wan Qian; Saringat, Mohd Zainuri (Applied Information Technology And Computer Science, 2025)
Chop Joo Huat Grocery Store is a grocery store with traditional sales and purchasing processes. The existing processes for recording customer orders and maintaining financial sales records are manual, error prone and time consuming. The objectives of this project are to design a grocery ordering system using an object-oriented approach, to develop a grocery ordering system using a web-based approach, and to test the functionality and usability of the developed grocery ordering system. The web-based grocery ordering system consists of eight modules including register, login, manage account details, manage groceries, manage order, manage payment, manage feedback, and generate report. The project used an iterative model of the software development life cycle to develop the system. At the end of the project, the grocery ordering system was successfully developed, and the reliability of the system was proved through testing, which indicated that the system met the user requirements.